Phosphate addition to urban waste composting, and residual phosphorus availability in forage sorghum. - Peixoto, Ricardo Trippia dos G.; Almeida, Dejair Lopes de; Franco, Avilio Antonio (Pesquisa Agropecuaria Brasileira, 2014)
The low agronomic efficiency of the Brazilian rock phosphates and the high industrial cost of soluble phosphates production, because of sulphur importation, request search for simplified utilization process of these raw materials. The possibility to increase the residual effect of phosphorus sources added before or after the urban waste composting by dry matter production and phosphorus absorption of forage sorghum (Sorghurn bicolor) was studied. A greenhouse experiment was conducted with a clayey Red-Yellow Latosel at three pH levels. The experimental design used was a factorial in randomized blocks. After culture of beans, the sorghum was sowed in the same pots as beans (Phaseolus vulgaris L.) and harvested 90 days after planting. The addition of rock phosphate of the urban waste before or after composting did not increase the availability of the residual phosphorus to sorghum, at any of pH levels studied. However, there was an increase of the residual phosphorus availability when the superphosphate was added before or after the urban waste composting, as well as at pH 4.8. This result shows the potential of organic waste management with more soluble phosphorus sources on acid soils.